The Use of Contact Lenses in Swimming and Scuba Diving - Hoelting, C; Egan, D J; Bennett, E S (Canadian Journal of Optometry, 1984)
The ametropic swimmer or scuba diver is at a disadvantage when engaging in these sports. This paper addresses some aspects of the problem, and offers some solutions as to the use of contact lenses: the effect of a wet environment on the physical properties of rigid and flexible materials, and how fitting characteristics may be affected; the pros and cons of both rigid and flexible contact lenses in swimming with and without goggles and masks; the professional person's advice in the above sporting activities when contact lenses are desired.